1993
DOI: 10.1182/blood.v81.12.3422.bloodjournal81123422
|View full text |Cite
|
Sign up to set email alerts
|

Pulse oximetry and factors associated with hemoglobin oxygen desaturation in children with sickle cell disease

Abstract: The observation of low transcutaneous arterial oxygen saturation (SaO2) in otherwise well sickle cell patients has lead to questions about the interpretation of pulse oximetry values in these patients. We undertook a prospective study of children with sickle cell disease to (1) determine the prevalence of, and factors associated with, low transcutaneous SaO2 in clinically well patients, (2) develop an algorithm for the use of pulse oximetry in acutely ill patients, and (3) assess the accuracy of pulse oximetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 0 publications
2
35
0
Order By: Relevance
“…This study is limited by the fact that arterial blood gases were not performed to confirm pO 2 and oxygen saturation, and some evidence suggests that pulse oximetry is not reliable in sickle cell disease (Blaisdell et al , 2000). However, a number of other studies have indicated that pulse oximetry is reliable for diagnosing hypoxia during steady state conditions and with acute complications in sickle cell disease patients (Rackoff et al , 1993; Kress et al , 1999; Ortiz et al , 1999). Another limitation of our study is that it is cross‐sectional rather than longitudinal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study is limited by the fact that arterial blood gases were not performed to confirm pO 2 and oxygen saturation, and some evidence suggests that pulse oximetry is not reliable in sickle cell disease (Blaisdell et al , 2000). However, a number of other studies have indicated that pulse oximetry is reliable for diagnosing hypoxia during steady state conditions and with acute complications in sickle cell disease patients (Rackoff et al , 1993; Kress et al , 1999; Ortiz et al , 1999). Another limitation of our study is that it is cross‐sectional rather than longitudinal.…”
Section: Discussionmentioning
confidence: 99%
“…Nocturnal oxygen desaturation is also a risk factor for stroke, silent infarct or seizure (Kirkham et al , 2001). On the other hand, reported associations of lower haemoglobin oxygen saturation with increased episodes of pain (Hargrave et al , 2003) and acute chest syndrome (Rackoff et al , 1993), manifestations of the vaso‐occlusive subphenotype, have not been confirmed in other studies (Quinn & Ahmad, 2005; Uong et al , 2006).…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) ≥160 ng/L has been used to define an elevated value in numerous previous studies 18‐21 . Hemoglobin oxygen saturation ≤ 95% has been suggested to identify SCD children at risk for hypoxia 22 . Glomerular filtration rate (GFR) <90 mL/minutes/1.73 m 2 is the cutoff that defines Stage I decline in GFR by Kidney Disease: Improving Global Outcomes (KDIGO) guidelines 23 .…”
Section: Methodsmentioning
confidence: 99%